Seed quality and soybean plasticity with different growth habits (Research, Society and Development, 2022)
This study aimed to evaluate the effect of the physiological quality of seeds on plastocrono, productivity and behavior of soybean cultivars. The experiment was conducted in the periods 2015/2016 and 2016/2017 in the middle plateau of the state of Rio Grande do Sul. Determined (BMX Active RR and Uranus RR FPS) and undetermined (5855 RSF IPRO and Don Mario 5958 RSF IPRO) cultivars were used. In each year of cultivation were conducted two trials in plant population and isolated plants from seeds with superior and inferior quality. The plastocrono was evaluated during the development of the plants and, at the end, the evaluation of productivity and production components was performed. The results were evaluated by analysis of variance and the mean values were compared by the Tukey test at 5%. The plastocrono was influenced by the availability of water, the form of growth was not determinant in the definition of plastocrono. Plants originated from seeds of lower quality need more plastocrono during its cycle. Plants of origin of seeds of superior quality produce more grains both in plant population and in isolation. Plant development was not a determining factor for productivity.